Removal of Vanadium and Nickel Ions from Iraqi Atmospheric Residue by Using Solvent Extraction Method - Ali, Noha Muhsen; Naife, Tariq Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
Iraqi crude Atmospheric residual fraction supplied from al-Dura refinery was treated to remove metals contaminants by solvent extraction method, with various hydrocarbon solvents and concentrations. The extraction method using three different type solvent (n-hexane, n-heptane, and light naphtha) were found to be effective for removal of oil-soluble metals from heavy atmospheric residual fraction. Different solvents with using three different hydrocarbon solvents (n-hexane, n-heptane, and light naphtha) .different variables were studied solvent/oil ratios (4/1, 8/1, 10/1, 12/1, and 15/1), different intervals of perceptual (15, 30-60, 90 and 120 min) and different temperature (30, 45, 60 and 90 °C) were used. The metals removal percent were found depending on the yield of asphaltene. The solvent-oil ratio had important effects on the amount of metal removal. The metals removal was increased at increasing temperatures from 30 to 90 0C increases the metal ion precipitated. The highest Ni precipitated was 79.23 ppm using heptane at 90 0C while for V the highest value was 64.51 ppm using also heptane at 90 0C, while the mixing time decreased metals removal. With increasing asphalt yield, the removal of metal was more selective. Among the solvents used in the extraction treatment method, the highest Ni precipitated was 76 ppm using hexane at 150 ml solvent and showed the most promising results. Increasing mixing time increases metals removal for V, the highest value was 65.51 ppm using either heptane or light naphtha.   The highest Ni precipitated was 78 ppm using heptane at 120 min while for V the highest value was 67 ppm using either heptane or light naphtha after 120 min.